Prognostic value of the immune target CEACAM6 in cancer: a meta-analysis - Burgos, Miguel; Cavero Redondo, Iván.; Álvarez Bueno, Celia.; Galán Moya, Eva María.; Pandiella, Atanasio; Amir, Eitan; Ocaña, Alberto (SAGE Publications Inc., 2022)
Background: Identification of membrane proteins differentially expressed on tumor cells is a key step in drug development. The carcinoembryonic antigen-related cell adhesion molecule 6 (CEACAM6) is a cell adhesion protein belonging to the immunoglobulin superfamily. Here, we explore the prognostic role CEACAM6 expression on patient outcome in cancer. Methods: A systematic search for studies evaluating the association between tumor expression of CEACAM6 and overall survival (OS) and disease-free survival (DFS) was performed. Hazard ratios (HR) were pooled in a meta-analysis using generic inverse variance and random effect modeling. Subgroup analyses were conducted based on tumor type and method of HR extraction. Results: Sixteen studies met the inclusion criteria. CEACAM6 expression was associated with worse OS [HR = 1.96, 95% confidence interval (CI) = 1.51–2.53], and DFS (HR = 2.49, 95% CI = 2.01–3.07) with subgroup analysis showing no significant differences between disease site subgroups. Conclusions: High expression of CEACAM6 is associated with worse OS and DFS in different malignancies. CEACAM6 is a target for the future development of novel therapeutics.
Keywords: CEACAM6; Disease outcome; Immunotherapy; Meta-analysis